CBMS-09 Intercellular communication at glioblastoma stem cell niches. (28th November 2020) - Hide, Takuichiro; Shirakawa, Yuki; Jono, Hirofumi; Shibahara, Ichiyo; Inukai, Madoka; Shinojima, Naoki; Mukasa, Akitake; Kumabe, Toshihiro
Abstract: Glioblastoma multiforme (GBM) contains heterogenous population of cells including a small population of GBM stem cells (GSCs), which potentially cause therapeutic resistance and tumor recurrence. GSCs harbored in special microenvironments, such as perinecrotic niche, perivascular niche, border niche. However, the mechanisms underlying the pathogenesis and maintenance of GSCs remain largely unknown. Stemness and chemo-radioresistance was promoted by not only additional mutation, but also microenvironment of GBM cells. Previously, we had reported that growth factors and cytokines secreted by oligodendrocyte lineage cells and macrophages/microglia induce stemness and chemo-radioresistance into GBM cells. Recently, Ito et al. reported that incorporation of ribosomes and ribosomal proteins into somatic cells promoted lineage trans-differentiation toward multipotency. Ribosomal proteins exist intra- and extracellularly. There is a possibility that ribosomal proteins promote stemness into cancer cells, we focused on 40S ribosomal protein S6 (RPS6), which is related to cell proliferation in lung and pancreatic cancer, but not reported in GBM. RPS6 was significantly upregulated in high-grade glioma. SiRNA-mediated RPS6 knock-down significantly suppressed the characteristics of GSCs, including their tumorsphere potential and stemness marker expression, such as Nestin and Sox2. RPS6 overexpression enhanced the tumorsphere potential of GSCs. Moreover, RPS6 expression was significantly correlated with SOX2 expression in different glioma grades. Immunohistochemistry data indicated that RPS6 was predominant detected at GSC niches, concurrently with the data from IVY GAP databases. Furthermore, RPS6 and other ribosomal proteins were upregulated in GSC-predominant areas in this database. The present results indicate that, in GSC niches, ribosomal proteins play crucial roles in the development and maintenance of GSCs and are clinically associated with chemo-radioresistance and GBM recurrence. These results suggested that intercellular communications through growth factors, cytokines, and ribosomes are regarded as new treatment targets of GBM.